Optimizing fertilizer use for sustainable food systems: an evaluation of integrated water-fertilizer system adoption among cotton farmers in China - Yuan, Yinghui; Wang, Changyi; Zai, Xueming; Song, Yulan; Zhang, Xiaoheng (Frontiers in Sustainable Food Systems, 2023)
Introduction In the face of escalating apprehensions surrounding food security, the sustainability of food systems, and food quality, the ingenuity of resource management strategies becomes paramount. A key component within these strategies is the enhancement of chemical fertilizer utilization, an element that bears significant weight on agricultural yields and the preservation of our environment. The emergence of Integrated Water-Fertilizer Systems (IWFS) thus presents a significant innovation in boosting the efficiency of chemical fertilizer usage, necessitating in-depth examination. Methods Utilizing a rigorous analytical framework that combines meta-frontier production function with a Two-Stage Residual Inclusion model, this study delves into the multi-dimensional impacts of IWFS adoption on fertilizer use efficiency among cotton growers in Xinjiang, China. Results Empirical evidence demonstrates that those who have adopted IWFS achieve a fertilizer use efficiency score of 0.452, markedly outstripping the mean score of 0.382 among non-adopters. Intriguingly, efficiency increases proportionately with the size of the farm, hinting at a sophisticated interplay between the adoption of technology and operational parameters. Discussion The research further unveils additional benefits including augmented cotton yields and diminished labor inputs among adopters. These multifaceted outcomes bear significant policy implications, highlighting the transformative potential of IWFS in promoting sustainable food systems, bolstering food security, and enhancing food quality.